2004
DOI: 10.1073/pnas.0404686101
|View full text |Cite
|
Sign up to set email alerts
|

Local modulation of plus-end transport targets herpesvirus entry and egress in sensory axons

Abstract: The core structures of many viruses move within cells by association with host cytoskeletal motor proteins; however, the mechanisms by which intracellular viral particles are transported toward sites of replication or the cell periphery at distinct stages of infection remain to be understood. The regulation of herpesvirus directional transport in sensory neurons was examined by tracking individual viral capsids within axons at multiple frames per s. After entry into axons, capsids underwent bidirectional and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
181
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(202 citation statements)
references
References 50 publications
20
181
1
Order By: Relevance
“…For egress, retrograde transport was the same speed as entry (suggesting the same motor was recruited, i.e. dynein) while anterograde transport was now faster resulting in nett move-HSV transport and egress HSV transport and egress 45 45 Copyright [105,129]. It was concluded that the activity of the anterograde motor (assuming the same kinesin was recruited during entry and egress) is directly regulated by the viral cargo [129] as has been suggested for cellular cargo [130].…”
Section: Bi-directional Viral Transportmentioning
confidence: 73%
See 3 more Smart Citations
“…For egress, retrograde transport was the same speed as entry (suggesting the same motor was recruited, i.e. dynein) while anterograde transport was now faster resulting in nett move-HSV transport and egress HSV transport and egress 45 45 Copyright [105,129]. It was concluded that the activity of the anterograde motor (assuming the same kinesin was recruited during entry and egress) is directly regulated by the viral cargo [129] as has been suggested for cellular cargo [130].…”
Section: Bi-directional Viral Transportmentioning
confidence: 73%
“…Direct interaction of DYNC1I and KLC also implies that kinesin bound to cargo can recruit and coordinate the activity of dynein and vice versa [128]. Measurements in real-time of GFP-pUL35-labelled PrV in chick DRGs indicates that herpesvirus capsid transport during entry and egress, at least within axons, is also bi-directional [105,129]. For PrV entry, movement was observed in both directions but the speed of retrograde transport was greater than anterograde transport resulting in net movement up the axon [129].…”
Section: Bi-directional Viral Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of this transport is bi-directional [5,6], including mRNA particles [7], mitochondria [2,8], virus particles [9,10], neuronal vesicles [11], etc. Typically, travel in a given direction (a "run") is short (1-2 μm) [1] though longer runs (~10 μm) are observed in some systems [10,12,13]. This observation is surprising since in vitro work suggests that when cargos are moved by multiple motors, they have very long run lengths [6,14,15].…”
Section: Introductionmentioning
confidence: 99%